(NmUZYKALXNOE ISKUSSTWO PAMIRAs (NKNIGA PERWAQs - (Nf(B. (NkAROMATOW(B.s; (Nn(B. (NnURDVANOWs ((NmOSKWAs (NsOWETSKIJ KOMPOZITORs, 1978)
(NpAMIR(B-(NSAMAQ WYSKAQ W sOWETSKOM sO@ZE STRANA GOR(B.s
Keywords: (NISTORIQs